Por uma psicanálise laica - Zygouris, Radmila (Percurso, 2010)
Realização: Andréa Carvalho, Bela M. Sister, Danielle M. Breyton, Deborah Cardoso, Silvio Hotimsky e Susan Markuszower Tradução: Andréa Carvalho e Danielle M. Breyton